The Role of Teachers to Enhance Students’ Learning Motivation: Challenges and Solutions - Giswa Aria Nanda (Presscience, 2024)
This study aims to explore the role of teachers in enhancing students' learning motivation, the challenges they face, and the solutions implemented to overcome these challenges. The research was motivated by observations of fluctuating learning motivation among students at a Islamic senior high school in Surakarta, Indonesia, influenced by environmental factors, peer dynamics, and individual character traits. These fluctuations manifest in low enthusiasm for learning, reluctance to participate in class activities, and delays in completing and submitting assignments. Recognizing the need for improvement in students’ motivation, this descriptive qualitative research adopts a phenomenological design to provide an in-depth understanding of the issue. The findings reveal that teachers play a crucial role in enhancing students’ motivation through the adoption of appropriate learning methods, leveraging technological tools, and designing supplementary programs. However, teachers encounter significant challenges, including diverse student characteristics, limited school resources, and high budget requirements. To address these challenges, teachers employ strategies such as offering personalized assistance and supervision, optimizing available learning facilities, and creating an initial budget plan for activities. This study underscores the importance of innovative and adaptive approaches by teachers to foster a more motivated learning environment.